Audit Delay : Influencing Factors (Case Study Of Large Trading Companies On The Indonesia Stock Exchange For The Period 2017 – 2021) - Astuti, Astuti; Dewi Nainggolan, Christine; Dermawan Sembiring, Lenny (International Journal of Science, Technology & Management, 2023)
The timeliness of the delivery of financial statements is an important factor in presenting relevant information. Obstacles in the accuracy of the submission of financial statements can certainly affect the market's response to the financial statements presented. This study aims to analyze the factors that affect audit delay, including company size, leverage and profitability. The implementation of the study was carried out on thirteen Large Trading Companies during the 2017-2021 period which totaled 65 data. The data analysis techniques used in this study are descriptive statistical analysis, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The results showed that partially the company size has a significant effect on audit delay, leverage has a significant effect on audit delay, while profitability has no significant effect on audit delay.